Lean Enterprise Software and Systems First International Conference, LESS 2010, Helsinki, finland, October 17-20, 2010, Proceedings - Abrahamsson, Pekka; Oza, Nilay (Lecture Notes in Business Information Processing, 2010)
The LESS 2010 conference was the first scientific conference dedicated to advancing the "lean enterprise software and systems" body of knowledge. It fostered interactions by joining the lean product development community with the agile community coupled with innovative ideas nurtured by the beyond budgeting school of thinking. The conference was organized in collaboration with the Lean Software and Systems Consortium (LSSC). The conference is established as a conference series. The idea of the conference was to offer a unique platform for advancing the state of the art in research and practice by bringing the leading researchers and practitioners to the same table. Indeed, LESS 2010 attracted a unique mix of participants including academics, researchers, leading consultants and industry practitioners. The aim of the conference was to use this diverse community to advance research and practical knowledge concerning lean thinking within the field of software business and development. LESS 2010 had more than 60% of its speakers come from the industry and the remaining from academia. LESS is poised to grow as we advance into future iterations of the conference and become the conference for lean thinking in systems and software development. Its growth and credibility will be advanced by the communities and knowledge exchange platform it provides. LESS offers several avenues for knowledge exchange to create a highly collaborative environment. Each year, we aim to bring novelty to a program that fosters collaboration, letting new ideas thrive during and after the conference.